Deploying Raspberry Pi in the classroom - Hart-Davis, Guy (Apress, 2017)
This book is for anyone who's looking to deploy Raspberry Pi computers in a classroom or lab situation and explains how to navigate the hardware and software choices you face. Deploying Raspberry Pi in the Classroom equips you with the skills and knowledge to plan and execute a deployment of Raspberry Pi computers in the classroom. Teachers and IT administrators at schools will see how to set up the hardware and software swiftly on your own or with the help of your students. Step-by-step instructions and practical examples walk you through building your Raspberry Pi workstations and your network, managing the computers and the network, and troubleshooting any problems that arise. This book offers several points to involve your students through hands-on activities. These activities are designed to benefit your beginner and older or more able students alike. Make Deploying Raspberry Pi in the Classroom a part of you instructional library today.
Includes bibliographical references and index. - Print version record
Keywords: Raspberry Pi (Computer); Computer science; Microprogramming; Programming languages (Electronic computers); Electronic Data Processing; Raspberry Pi (Ordinateur); Informatique; Microprogrammation; Algorithms & data structures; Programming & scripting languages: general; Computer hardware; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference